2006
DOI: 10.1007/s10616-006-9038-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12, a chlorophyll-related analog to pheophytin a from marine brown algae, promotes neurite outgrowth and stimulates differentiation in PC12 cells

Abstract: We previously isolated an analog to chlorophyll-related compounds, pheophytin a, from the marine brown alga Sargassum fulvellum and demonstrated that it is a neurodifferentiation compound. In the current study, we investigated the effects of the pheophytin a analog vitamin B 12 on PC12 cell differentiation. In the presence of a low level of nerve growth factor (10 ng ml -1 ), vitamin B 12 demonstrated neurite outgrowthpromoting activity in PC12 cells. The effect was dose-dependent in the range of 6-100 lM. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…However, diet containing 2% seaweed significantly(P<0.05) increased Ht and Hb of heat stressed lambs (T0, Table 6). In accordance with the present results, Ina and Kamei (2006) and García-Casal et al (2009) reported that marine brown seaweeds especially Sargassum spp. are good sources of anti-anemic agents such as iron and vitamins B.…”
Section: Hematological Parameterssupporting
confidence: 93%
“…However, diet containing 2% seaweed significantly(P<0.05) increased Ht and Hb of heat stressed lambs (T0, Table 6). In accordance with the present results, Ina and Kamei (2006) and García-Casal et al (2009) reported that marine brown seaweeds especially Sargassum spp. are good sources of anti-anemic agents such as iron and vitamins B.…”
Section: Hematological Parameterssupporting
confidence: 93%
“…There are many specialists occupied with discovering natural antioxidants posing security and adequacy, which can be replaced the manufactured ones butylated hydroxyl anisole (BHA), butylated hydroxyl toluene (BHT), α-tocopherol and propyl gallate which led to destroying the liver and causing cancer [ 28 ]. Ina and Kamei [ 29 ] classified the algal antioxidants into two groups; (1) water-soluble antioxidants vitamins, phycobiliproteins and polyphenols, and (2) fat-soluble antioxidants carotenoids and vitamin E (α-tocopherol).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Ina and colleagues demonstrated that the neurodifferentiation of PC12 cells by pheophytin a of Sargassum fulvellum required the presence of NGF and involved the activation of an MAPK signaling pathway [ 147 ]. Vitamin B 12 , a chlorophyll-related analog to pheophytin a, also stimulated NGF-dependent PC12 cell differentiation by an MAPK signaling pathway [ 148 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%